IMPLEMENTASI TEKNOLOGI ARTIFICIAL INTELEGENCE DALAM BIDANG PENDIDIKAN - Darwis, Umar (JURNAL ILMU PENDIDIKAN, 2024)
Abstract Artificial Intelligence (AI) is a term from Industrial Society 4.0 and Society 5.0. which is a "computer program, machine learning, hardware and software". Artificial Intelligence uses a science of hardware and software inspired by reverse engineering of the neocognitron patterns that work in the human brain. These Industry 4.0 products are widely used in development and daily applications in various fields, including education. The aim of this research is to clarify the role of AI in education, and the method used is a qualitative research method. In the world of education, artificial intelligence is used to personalize each student's learning. This AI system helps create a learning profile for each student, allowing learning materials to be tailored to each student's abilities, learning style and experience. The implementation of AI technology in the education sector makes things easier for educators in various matters, especially in the administrative sector, such as determining final grades based on weights and assessments, creating more active learning, and making the tasks of teachers and students easier in learning and teaching activities. Keywords: Artificial Intelligence, Technology Implementation, Education